Explanation:
1).
![(x)/(8) = (9)/(24)](https://img.qammunity.org/2021/formulas/mathematics/high-school/1ypvtggg1aeinzru436yiyrt0peollato0.png)
Cross multiply
We have
24x = 72
Divide both sides by 24
That's
![(24x)/(24) = (72)/(24)](https://img.qammunity.org/2021/formulas/mathematics/high-school/21cqen0e5rgwvz05gkejv1fx3ty79y9fg4.png)
We have the answer as
x = 3
2).
3x² + 2x - 10
when x = - 1
Substitute the value of x into the expression
That's
3(-1)² + 2(-1) - 10
= 3 - 2 - 10
We have the answer as
- 9
When x = 0
That's
3(0) + 2(0) - 10
= - 10
When x = 1
That's
3(1)² + 2(1) - 10
= 3 + 2 - 10
= 5 - 10
= - 5
3).
![√(( - 9))](https://img.qammunity.org/2021/formulas/mathematics/high-school/brk2myk9dv02x4treaae0di7ubpvy4pluf.png)
First of all apply the radical rule
That's
![√( - a) = √( - 1) * √(a)](https://img.qammunity.org/2021/formulas/mathematics/high-school/4qm23zhrtoagf3yuy4zuanib5wi4yj9kaa.png)
So we have
![√( - 9) = √( - 1) * √(9)](https://img.qammunity.org/2021/formulas/mathematics/high-school/rjt8kuzh1xunpuuiusn8syfc4koqy4clj2.png)
Using the imaginary rule
That's
![√( - 1) = i](https://img.qammunity.org/2021/formulas/mathematics/college/7cqe7d5gfjfo8acoehinhx8o2mz043mruh.png)
We have
![√(9) * i](https://img.qammunity.org/2021/formulas/mathematics/high-school/ber7kh1ffqwglwoeb5mt5o3sixw4edek34.png)
We have the final answer as
3i
4).
![(1)/(x)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/luq4pd2447ddu0h1t98mosx4i8gqqnk37c.png)
when x = 0
We have
![(1)/(0) = 0](https://img.qammunity.org/2021/formulas/mathematics/high-school/yzb5u06scytkmqm6ap6elarcveifc6lijd.png)
when x = 1
![(1)/(1) = 1](https://img.qammunity.org/2021/formulas/mathematics/high-school/ik7ig9m63n9wy7vquot3njwedu4t4c17hq.png)
when x = 2
We have
![(1)/(2)](https://img.qammunity.org/2021/formulas/physics/middle-school/ukxexrkoplrwscaxd96qbbkphc5fo6w2ur.png)
Hope this helps you